Comparison of Methods for the Recovery of Virus Inoculated into Ground Beef - Tierney, John T. (1973)
Various methods for the recovery of virus inoculated into ground beef were investigated in an attempt to develop a sensitive system that could be used to detect viral contaminants in market foods. A 100-g sample, inoculated with poliovirus 1, was suspended in 150 to 900 ml of Eagle minimum essential medium, pH 8.5, and mixed in either plastic bags or plastic cups on a mechanical shaker. The particulate materials were removed by means of cheese cloth, glass wool, woven fiber glass, or low-speed centrifugation. Large volumes of fluid were concentrated by ultrafiltration. Microbiological contamination was controlled by high antibiotic concentrations or by filtration. Quantitative plaque-forming-unit recovery of the virus was determined by utilizing an agar overlay technique on Vero cell cultures. The data indicated that from 20 to 50% of the seeded virus could be recovered from a 100-g sample of ground beef. The glass wool and woven fiber glass methods were the most effective, with recovery of approximately 50% of the inoculated virus.